OPTIMALISASI KREATIVITAS SISWA MELALUI PENERAPAN PENDEKATAN STEAM PADA MATERI ENERGI DAN ZAT DI SEKITAR KITA (STUDI KASUS DI KELAS III UPTD SDN 18 PEUSANGAN) - Rina, Cut; Maisura; M. Danil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Creativity is one of the essential competencies that elementary school students need to develop in order to respond to the challenges of twenty-first-century learning. However, classroom learning practices are often dominated by teacher-centred instruction, resulting in limited opportunities for students to explore ideas, solve problems creatively, and produce meaningful learning products. This study aimed to describe the implementation of the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach in the topic of Energy and Matter Around Us and to describe students’ creativity following the implementation of the approach in Grade III of UPTD SD Negeri 18 Peusangan. This study employed a qualitative descriptive approach. The research participants consisted of one classroom teacher and all Grade III students of UPTD SD Negeri 18 Peusangan. Data were collected through observation, interviews, documentation, and creativity assessment sheets. Data analysis included data reduction, data display, and conclusion drawing. The findings indicate that the implementation of the STEAM approach was carried out through four stages: observation, idea development, design and experimentation, and product creation and presentation. The integration of science, technology, engineering, arts, and mathematics encouraged students to participate actively in learning activities and provided opportunities for them to develop ideas creatively. Students demonstrated creativity through fluency in expressing ideas, flexibility in solving problems, originality in producing products, and elaboration in refining their work. The study concludes that the STEAM approach effectively optimizes students’ creativity in learning the topic of Energy and Matter Around Us in elementary school.